2017
DOI: 10.1177/0363546517707196
|View full text |Cite
|
Sign up to set email alerts
|

Chondral Injuries and Irreparable Meniscal Tears Among Adolescents With Anterior Cruciate Ligament or Meniscal Tears Are More Common in Patients With Public Insurance

Abstract: In adolescent patients with ACL or meniscal tears, patients with public insurance had a more delayed presentation than those with private insurance. They also tended to have more moderate-to-severe chondral injuries and meniscal tears, if present, that required debridement rather than repair. More rapid access to care might improve the prognosis of young patients with ACL and meniscal injuries with public insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 14 publications
(39 reference statements)
1
54
1
Order By: Relevance
“…Although male sex and revision surgery were most strongly associated with both BCLs and glenoid bone loss, patient race, specifically black race, was also independently associated with BCLs and glenoid bone loss involving >10% of the glenoid width, which is a novel finding worth noting. Although several nonmodifiable patient demographic and social factors have been shown to influence access to care for similar sports medicine procedures routinely performed in young, active patients, 27,30,43 further study of this particular finding in patients with shoulder instability is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although male sex and revision surgery were most strongly associated with both BCLs and glenoid bone loss, patient race, specifically black race, was also independently associated with BCLs and glenoid bone loss involving >10% of the glenoid width, which is a novel finding worth noting. Although several nonmodifiable patient demographic and social factors have been shown to influence access to care for similar sports medicine procedures routinely performed in young, active patients, 27,30,43 further study of this particular finding in patients with shoulder instability is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with previous studies that have found similar associations between health insurance type and prevalence of additional knee injuries. [5,21]…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a recent study reported that 14% of patients undergoing ACL reconstruction had Medicare, Medicaid, or other government-sponsored insurance, which is an almost 3-fold increase from 5% in 1996. 3 We hypothesized that government-sponsored health care would put patients at an increased risk of MUA/LOA, as numerous studies have reported a decrease or lag in access to care for this patient population, 2 , 16 , 24 and because we have noticed from our own experience that it is often more difficult for these patients to access physical therapy both preoperatively and postoperatively. The results of this study do not support this hypothesis, as the relative risk for undergoing MUA/LOA after ACL reconstruction for patients enrolled in government-sponsored health care was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%